Transplant center practices that maximize access to living kidney transplantation: the Penn experience - Arpali, Emre; Abu-Gazala, Samir; Redfield, Robert R.; Leonberg-Yoo, Amanda; Dunn, Ty B. (Frontiers in Immunology, 2026)
Living donor kidney transplantation (LDKT) provides superior outcomes for patients with end-stage kidney disease (ESKD) but remains underutilized due to persistent barriers including donor-recipient incompatibility, financial concerns, and limited donor outreach. This study describes a center-based strategy implemented at Penn Medicine’s Center for Living Donation to specifically address these challenges and expand access to LDKT. Key components included the development of a dedicated infrastructure for donor evaluation, the integration of Living Donor Navigators to guide and support donors, and the use of personalized microsites through the National Kidney Registry (NKR) to facilitate recipient-driven outreach. Financial barriers were reduced through accessing national assistance programs, while participation in kidney paired donation and the NKR Voucher Program enabled flexibility in overcoming immunologic and timing obstacles. This coordinated approach resulted in a substantial increase in living donor transplants, including more than 100 KPD transplants in a single year—a global record. Donor and recipient satisfaction was consistently high, underscoring the effectiveness of the center’s patient-centered model. These findings demonstrate the impact of structured and scalable interventions designed to enhance access to LDKT. The Penn model offers a practical framework for other transplant centers seeking to reduce barriers and expand living kidney donation.